Molecular Modelling and In Vitro Research of New Substances for the Targeted Stimulation of AQP3 in Skin - Viktor Filatov; Andrey Varava; Egor Ilin (Chemistry Proceedings)
Skin dryness and xerosis are the most common clinical manifestations of different dermatological diseases. At the same time, it was established that the expression of aquaporin 3 (AQP3) is related to the pathogenesis of atopic dermatitis, psoriasis, eczema, and vitiligo. Thus, our study was focused on the search for new molecules and the investigation of their biological activity to accelerate the expression of AQP3 in the skin’s epidermis. Aloin from an Aloe barbadensis leaf extract and trimethylglycine were chosen as new potential candidates using DiffDock computational modelling. These natural molecules demonstrated a good affinity towards the active site of AQP3 with an estimated docking score of −6.2 kcal/mol to −7.7 kcal/mol. Phyto4Health modelling predicted the anti-psoriatic, anti-inflammatory, and immunosuppressant activities that are useful in the treatment of atopic skin diseases. Furthermore, it was shown that the combination of the Aloe barbadensis leaf extract and trimethylglycine in a mass ratio of 1:1 revealed a clear synergetic effect to increase the AQP3 amount up to two times. Thus, the combination of the Aloe barbadensis extract standardized for aloin and trimethylglycine has a promising potential in drug development and the treatment of dryness.